2021
DOI: 10.3390/cancers13184640
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas13-Based Platforms for a Potential Next-Generation Diagnosis of Colorectal Cancer through Exosomes Micro-RNA Detection: A Review

Abstract: Colorectal cancer (CRC) is the third most prevalent cancer with the second highest mortality rate worldwide. CRC is a heterogenous disease with multiple risk factors associated, including obesity, smoking, and use of alcohol. Of total CRC cases, 60% are diagnosed in late stages, where survival can drop to about 10%. CRC screening programs are based primarily on colonoscopy, yet this approach is invasive and has low patient adherence. Therefore, there is a strong incentive for developing molecular-based methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 195 publications
(237 reference statements)
0
9
0
Order By: Relevance
“…Recent studies have shown that the overall sensitivities can be around 76%, with a similar specificity level, which means there is potential for future use in screening and early detection. There have been numerous candidate miRNAs including miR-21 [113] and miR-23a [114]. Another miRNA candidate, miR-378 has been found to affect signaling pathways that control processes such as cell proliferation and apoptosis, specifically in stage II CRC [115].…”
Section: Micrornas and Other Non-coding Rnasmentioning
confidence: 99%
“…Recent studies have shown that the overall sensitivities can be around 76%, with a similar specificity level, which means there is potential for future use in screening and early detection. There have been numerous candidate miRNAs including miR-21 [113] and miR-23a [114]. Another miRNA candidate, miR-378 has been found to affect signaling pathways that control processes such as cell proliferation and apoptosis, specifically in stage II CRC [115].…”
Section: Micrornas and Other Non-coding Rnasmentioning
confidence: 99%
“…On the other hand, some of the most relevant miRNA molecules assessed, such as miR-145, miR-143, miR-135, and miR-17-92, showed a significant diagnostic value for advanced neoplasia [86]. Furthermore, a recent study has used SHERLOCK-based miRNA detection to enhance and facilitate exosome-miRNA detection in blood, showing miR-126, miR-1290, miR-23a, and miR-940 as the best predictive biomarkers for early CRC stages [87]. Other miRNAs have been described as potential biomarkers, such as miR-92a, miR-29a, miR-125b, miR-19a-3p, miR-223-3p, miR-92a-3p and miR-422a, although miR-21 is by far the most studied for CRC [78].…”
Section: Transcriptomicsmentioning
confidence: 99%
“…This method could be suitable for personalized cancer modeling and tumor-driven analysis in the future to provide guidance for precision medicine. In recent years, as microRNAs have been reported to be associated with tumorigenesis, diagnosis, and prognosis, the CRISPR/Cas technology promises great potential for an early diagnosis of miRNA-related disease[ 38 , 39 ]. Qiu et al [ 40 ] developed the RCA-CRISPR-split-HRP (RCH) detection system based on dCas9, which facilitated CRISPR/Cas9 technology in miRNA detection for the first time.…”
Section: Clinical Application Of Crispr/cas Technologymentioning
confidence: 99%